1993
DOI: 10.1161/01.str.24.7.1049
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the vasodilator response to vasopressin in canine cerebral arteries in vivo.

Abstract: Background and Purpose: The aim of this study was to investigate the regional differences in the in vivo vasodilator responses to vasopressin, which is thought to stimulate the release of nitric oxide from the endothelium, in canine cerebral arteries by angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…63,91 There are significant differences in the ability of different arteries to vasodilate in response to vasopressin; for instance, arteries of the circle of Willis are more sensitive to the vasodilatory effects of vasopressin than are other intracranial and extracranial arteries. 92 The receptor subtype responsible for vasodilation is uncertain. The V2 receptor agonist 1-desamino-8-D-arginine vasopressin causes a decrease in BP and facial flushing in humans 93 and peripheral vasodilatation in dogs.…”
Section: Vasodilator Effectsmentioning
confidence: 99%
“…63,91 There are significant differences in the ability of different arteries to vasodilate in response to vasopressin; for instance, arteries of the circle of Willis are more sensitive to the vasodilatory effects of vasopressin than are other intracranial and extracranial arteries. 92 The receptor subtype responsible for vasodilation is uncertain. The V2 receptor agonist 1-desamino-8-D-arginine vasopressin causes a decrease in BP and facial flushing in humans 93 and peripheral vasodilatation in dogs.…”
Section: Vasodilator Effectsmentioning
confidence: 99%
“…In Vivo Studies. It has been reported that intravenous or intracisternal injections of NOS inhibitors constrict pial arterioles in the cerebral cortex and arteries in the basal brain, such as anterior, middle and posterior cerebral arteries or decrease cortical cerebral blood flow in the mouse (Rosenblum et al, 1990), rat (Faraci, 1990(Faraci, , 1991Prado et al, 1992;Kelly et al, 1995;Yang, 1996), dog (Suzuki et al, 1993b;Toda et al, 1993bToda et al, , 2000a, pig (Armstead, 1995b;Rebich et al, 1995), goat (Fernandez et al, 1995), and monkey (Okamura et al, 1995a;Toda et al, 2000b). Intraperitoneal injections of 7-nitroindazole, a selective nNOS inhibitor, decreased cerebral blood flow without modifying the systemic blood pressure in awake rats (Montecot et al, 1997) and decreased cerebral capillary flow in anesthetized rats (Hudetz et al, 1998).…”
Section: Nerve Stimulation By Electrical Pulses and Bymentioning
confidence: 99%
“…In animal studies, the administration of vasopressin, however, also increases CBF by dilating cerebral arteries. [15][16][17] Vasopressin also may regulate regional CBF by balancing the effects of increased flow mediated by nitric oxide released from the endothelium, with decreased flow in vessels contracted by direct stimulation of smooth muscle. 18 It has been postulated that the increase in CBF may be mediated through cerebral V2 receptors.…”
mentioning
confidence: 99%